Public health preparedness and responses to the coronavirus disease 2019 (COVID-19) pandemic in South Asia: a situation and policy analysis - Amitabha Sarkar; Guangqi Liu; Yinzi Jin; Zheng Xie; Zhi-Jie Zheng (Global Health Journal, 2020)
Like rest of the world, the South Asian region is facing enormous challenges with the coronavirus disease 2019 (COVID-19) pandemic. The socioeconomic context of the eight South Asian countries is averse to any long-term lockdown program, but the region still observed stringent lockdown close to two months. This paper analyzed major measures in public health preparedness and responses in those countries in the pandemic. The research was based on a situation analysis to discuss appropriate plan for epidemic preparedness, strategies for prevention and control measures, and adequate response management mechanism. Based on the data from March 21 to June 26, 2020, it appeared lockdown program along with other control measures were not as effective to arrest the exponential growth of fortnightly COVID-19 cases in Afghanistan, Bangladesh, India, Nepal and Pakistan. However, Bhutan, Maldives and Sri Lanka have been successfully limiting the spread of the disease. The in-depth analysis of prevention and control measures espoused densely populated context of South Asia needs community-led intervention strategy, such as case containment, in order to reverse the growing trend, and adopt the policy of mitigation instead of suppression to formulate COVID-19 action plan. On the other hand, mechanism for response management encompassed a four-tier approach of governance to weave community-led local bodies with state, national and international governance actors for enhancing the countries’ emergency operation system. It is concluded resource-crunch countries in South Asia are unable to cope with the disproportionate demand of capital and skilled health care workforce at the time of the pandemic. Hence, response management needs an approach of governance maximization instead of resource maximization. The epidemiologic management of population coupled with suitable public health prevention and control measures may be a more appropriate strategy to strike a balance between economy and population health during the time of pandemic.